2012
DOI: 10.1371/journal.pone.0051151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel Bradykinin B1 Receptor Antagonist and Angiotensin II Receptor Blockade on Experimental Myocardial Infarction in Rats

Abstract: BackgroundThe aim of the present study was to evaluate the cardiovascular effects of the novel bradykinin B1 receptor antagonist BI-113823 following myocardial infarction (MI) and to determine whether B1 receptor blockade alters the cardiovascular effects of an angiotensin II type 1 (AT1) receptor antagonist after MI in rats.Methodology/Principal FindingsSprague Dawley rats were subjected to permanent occlusion of the left descending coronary artery. Cardiovascular function was determined at 7 days post MI. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Treatment with kinin B 1 receptor antagonist improved cardiac function after myocardial infarction, as evidenced by attenuation of elevated LV end diastolic pressure [28]. On the other hand, it was shown that tissue kallikrein, through the kinin B 2 receptor and NO formation, improves cardiac function, apoptosis, and inflammation, and limits LV remodeling after ischemic injury [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with kinin B 1 receptor antagonist improved cardiac function after myocardial infarction, as evidenced by attenuation of elevated LV end diastolic pressure [28]. On the other hand, it was shown that tissue kallikrein, through the kinin B 2 receptor and NO formation, improves cardiac function, apoptosis, and inflammation, and limits LV remodeling after ischemic injury [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…7,27 It exhibits high affinity (Ki) for both human and rat B1 receptors (5.3 and 13.3 nmol/L, respectively), whereas has no affinity for the B2 receptors (IC50>10.000 nmol/L). 27 BI 113823 does not influence blood pressure in conscious rats.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In contrast to the B2 receptormediated relaxation to bradykinin, B1 receptors mediate vasoconstriction in cardiopulmonary vascular beds. 8,10,11 We hypothesized that kinin B1 receptors may play an important role in the pathogenesis of PAH.…”
Section: -6mentioning
confidence: 99%
See 2 more Smart Citations